2021
DOI: 10.1016/j.genhosppsych.2021.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and behavioral cardiometabolic risk of children and young people on mental health inpatient units: A systematic review and meta-analysis

Abstract: Objective Serious mental illness is associated with physical health comorbidities, however most research has focused on adults. We aimed to synthesise existing literature on clinical and behavioral cardiometabolic risk factors of young people on mental health inpatient units. Methods A systematic review and meta-analysis was conducted, using electronic searches of PsycINFO, EMBASE, AMED, Cochrane Central Register of Controlled Trials, and Ovid MEDLINE. Eligible studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 64 publications
(225 reference statements)
0
15
0
Order By: Relevance
“…To summarize available research on medical and psychological metabolic abnormalities among adolescent mental health inpatients. They executed the meta-analysis ( 12 ). A convenience sample strategy was used to deliver an online survey among kids and teenagers ( 13 ).…”
Section: Study Backgroundmentioning
confidence: 99%
“…To summarize available research on medical and psychological metabolic abnormalities among adolescent mental health inpatients. They executed the meta-analysis ( 12 ). A convenience sample strategy was used to deliver an online survey among kids and teenagers ( 13 ).…”
Section: Study Backgroundmentioning
confidence: 99%
“…These physical health problems often go undetected and therefore untreated (Eapen & John, 2011). Furthermore, CYP with mental health disorders are at increased risk for engaging in behaviors which are detrimental to their physical health, such as tobacco smoking, alcohol consumption, unhealthy diet, and physical inactivity, compared with their peers (Carney et al, 2016(Carney et al, , 2021Eapen & John, 2011). Relatedly, CYP with mental health disorders also experience significantly more barriers to living a healthy, active lifestyle, than CYP without (Carney, Cotter, et al, 2017;Firth et al, 2016;Rosenbaum et al, 2016).…”
Section: The Importance Of Physical Health For Cyp With Mental Health...mentioning
confidence: 99%
“…This involves targeting wide-reaching community-based child and adolescent mental health services, using public health initiatives, as well as looking at those providing specialist inpatient care to people already exhibiting signs of ill-health or already prescribed psychotropic medications with substantial metabolic side-effects (Carney et al, 2021;Eapen & John, 2011;Galling & Correll, 2015) 3. Accredited exercise professionals should be used to deliver interventions, where possible.…”
Section: Recommendations For Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the common co-occurrence of SMI and substance use can leave individuals with serious mental illness at increased risk of infectious diseases (Hughes et al, 2016). A systematic review by Carney et al (2021) similarly found relatively poor physical health among young people in inpatient units compared to the general population. Behavioural risk factors for physical health conditions can also vary by mental health diagnosis (Firth et al, 2019).…”
Section: Introductionmentioning
confidence: 99%